PENGARUH PELAYANAN FISKUS DAN STRATEGI PENEGAKAN HUKUM TERHADAP KEPATUHAN WAJIB PAJAK USAHA KECIL MENENGAH KECAMATAN GEMPOL - Fuad, Achmad Nur (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2020)
Law Enforcement (Law Enforcement) is an activity to harmonize the relationships of values that are set out in the principles of solid values and attitudes not as a series of translation of the final stage of value to create, maintain, and maintain peace in the intercommunication of life. With the consistent law enforcement of taxation, it is one of the ways that taxation provisions can be obeyed by taxpayers so that there is no threat or coercion in paying taxes. The task of the taxation apparatus is to conduct various counseling and training so that the public is aware of their obligation to pay taxes, but to realize this is not easy and will be a big challenge for the tax authorities to make people aware of tax payments and in essence is to build how to make people aware of taxation law. Compliance of taxpayers is very important for the State to increase the state budget from tax revenue, therefore the need for attention from aspects of Fiscus Services provided to Small and Medium Enterprises taxpayers and Law Enforcement Strategies implemented by the government. Theopurposeofthis study wasto determine the effect of the tax authorities and law enforcement strategies ontaxcompliance in Gempol District. Datacollection methods usedwereobservationandquestionnaires. Theanalyticalmethodusedismultipleregressionanalysis. The results of this study are the tax authorities and law enforcement strategies have a partial effect on the level of compliance of taxpayers of small and medium enterprises with theoresults ofthetestused to determine each variable thataffectstheleveloftaxpayercompliance. To improve taxpayer compliance, it is necessary to have good tax management based on value, fairness, honesty, discipline of tax officers or tax officers (tax employees) and are guided by tax laws. Keywords : Fiscus Services, Law Enforcement Strategies and Compliance Taxpayers and Small and Medium Enterprises